MANAGEMENT STYLE OF HEAD OF ALIYAH STATE MADRASAH IN INCREASING MOTIVATION FOR ACHIEVEMENT OF EDUCATIONAL WORKERS IN JAMBI PROVINCE (SURVEY AT MAN 2 JAMBI CITY, MAN 2 BATANG HARI AND MAN 1 BUNGO) - Suyanto, Suyanto (Dinasti Publisher, 2022)
Based on the results of the grand tour that the researchers conducted at the Madrasah Aliyah Negeri in Jambi Province, the head of the madrasa has not correctly determined the planning of madrasa disciplinary guidelines. Second, the madrasa principal has not optimally made instructions, warnings, and prohibitions on behavior in madrasas such as carrying out continuous supervision of the discipline of education staff, and found a number of problems related to this. This study aims to analyze the management style of the head of Madrasah Aliyah Negeri in increasing motivation. education in Jambi Province. This descriptive qualitative research uses a descriptive qualitative approach. The subjects of this study were the Head of Madrasah Aliyah Negeri 2 Jambi City, Madrasah Aliyah Negeri 2 Batang Hari and Madrasah Aliyah Negeri 1 Bungo as key informants (respondents), deputy heads and education staff. Data collection with observation, interview, and documentation techniques. Data analysis using the Miles and Huberman model consists of data reduction, data display and data conclusion. The results of the research are: democratic style seen from task direction, task direction, decision making and relationships built. This will foster a democratic climate in schools, which will encourage the creation of a conducive climate for the creation of optimal quality of work. The achievement motivation of educational staff in Jambi Province is characterized by work responsibilities, standards, plans and work creativity. The principal's management style in increasing the achievement motivation of educational staff in Jambi Province is clear work directions, joint decision making and two-way relationships. and interactive, though spanning all tasks and personnel. Based on the findings of the study, it was concluded that the principal's management style in increasing the achievement motivation of educational staff in Jambi Province was not optimal because task direction, decision making and relationships were not productive.